The Intimate Archive: Gender, Memory, and Agency in Partition Narratives - Mahnoor Fatima; Muhammad Bilal Sarfraz; Muhammad Rehan Sabir; Alwy Ahmed Mohamed (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to criticize the historical narrative of the 1947 Partition of India that focuses too much on political and state aspects and ignores women's personal experiences. In addition, the concept of intimate archive was introduced to understand how women build meaning in life after violence. Theoretical framework: Approaches used include Feminist Historiography, Trauma Theory, and Critical Archive Studies to show that archives and testimonies are not objective, but rather the result of constructions influenced by power relations and individual experiences. Literature review: Previous literature has tended to focus on macro aspects such as politics and conflict. Instead, this study highlights the work of Saadat Hasan Manto and Amrita Pritam as well as feminist oral histories that describe women's experiences in a more personal and profound way. Methods: The method used is qualitative through close reading of literary works and oral history analysis to explore hidden meanings in women's experiences. Results: Three forms of intimate archive were found, namely meaning in objects, memories in the body, and the use of silence as a strategy. These findings show that women have an active role in shaping identity and meaning in life. Implications: The findings of the study expand the perspective of archives, not only as official data but also as representations of personal experiences. The concept of an intimate archive can also be applied to other studies that address marginalized experiences. Novelty: Novelty lies in the concept of an intimate archive that views testimony as an active process in building meaning, not just a record of experience.